SAT0226 Early Experience with Tofacitinib: Treatment Patterns in Two us Healthcare Claims Databases. (9th June 2015) - Harnett, J.; Curtis, J.; Gerber, R.; Gruben, D.; Koenig, A.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Limited data are available to describe the characteristics of patients (pts) with RA initiating tofacitinib and subsequent utilisation patterns in clinical practice. Objectives: To describe the characteristics of pts with RA initiating tofacitinib and evaluate adherence and costs using data from two US administrative claims databases. Methods: This was a retrospective cohort analysis of pts aged ≥18 years (yrs) with an RA diagnosis (ICD9: 714.xx) and ≥1 tofacitinib claim in the Truven Marketscan (TM) or Optum Clinformatics (OC) Commercial and Medicare healthcare claims databases. Index date was the first tofacitinib fill date (Nov 2012–June 2014). Pts were continuously enrolled for ≥12 months (mos) pre- and post-index. Pts with another inflammatory disease diagnosis and those who received a biologic prescription/administration within 14 days of index were excluded. Tofacitinib adherence was assessed using proportion of days covered (PDC), and 12-mo post-index RA-related costs were evaluated. Outcomes are stratified by whether pts were biologic-naïve (no biologic ≤12 mos of tofacitinib initiation) or biologic-experienced, and by receipt of tofacitinib alone (no conventional synthetic [cs]-DMARD ≤90 days of tofacitinib initiation) or with csDMARD. Results: Of pts who initiated tofacitinib, 337/2863 (11.8%) pts from TM and 118/1037 (11.4%) pts from OC met cohort selection criteria. Pt characteristics and Charlson Co-morbidity Index and claims-based index of RA severity scores were similar between database cohorts. Of pts receiving tofacitinib, 51–52% received it without concomitant csDMARD; 31–39% of pts were biologic-naïve in 12 mos pre-index. The 12-mo overall mean (median) PDC was 0.61 (0.67) in TM and 0.56 (0.58) in OC. There was no significant difference in PDC between pts receiving tofacitinib monotherapy vs combination therapy in TM and OC (Table ). Biologic-experienced pts in TM had significantly better adherence vs biologic-naïve pts; no significant differences in adherence were seen between biologic-naïve and biologic-experienced pts in OC (Table ). Mean (standard deviation) change in 12-mo RA-related outpatient and overall costs, respectively, were -1197 (10456) and 5118 (28699) in TM and -4930 (14761) and 1390 (26603) in OC. No significant differences in 12-mo post-index overall RA-related costs were observed between pts receiving tofacitinib monotherapy vs combination therapy in TM and OC and between pts with prior biologic use and biologic-naïve pts in OC; however, costs were significantly higher for biologic-experienced pts in TM (Table ). Conclusions: About half of pts received tofacitinib alone and approximately one-third of pts were biologic-naïve. One-yr mean adherence levels were within the previously reported PDC range for select TNFi. 1 Adherence and overall RA-related costs were similar regardless of monotherapy status in both database cohorts and by prior biologic use in OC; higher RA-related costs in biologic-experienced pts in TM may be related to greater adherence observed. References: Li P et al. Value Health 2010; 13: 805-812. Acknowledgements: This study was sponsored by Pfizer Inc. Editorial support was provided by Karen Irving at Complete Medical Communications and funded by Pfizer Inc. Disclosure of Interest: J. Harnett Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Curtis Grant/research support from: Pfizer Inc., R. Gerber Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., D. Gruben Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., A. Koenig Shareholder of: Pfizer Inc., Employee of: Pfizer Inc.